Changes in the nutritional value, flavor, and antioxidant activity of brown glutinous rice during fermentation. (October 2021) - Xu, Yue; Jin, Yamei; Su, Jiajia; Yang, Na; Xu, Xueming; Jin, Zhengyu; Cui, Bo; Wu, Fengfeng
Abstract: Effect of fermentation on the nutritional value, flavor, and antioxidant activity of sweet fermented brown glutinous rice were evaluated by determining its specific physical and chemical indexes. The results showed that the changes in nutrients, flavor, and antioxidant activity during brown glutinous rice fermentation were significant. Macromolecular polysaccharides such as starch were gradually degraded into low-molecular-weight polysaccharides that were mostly composed of glucose. The gradual hydrolysis of proteins led to increases in polypeptide and amino acid content. The total free amino acid content in brown glutinous rice fermented for 60 h was 1.785 times the content obtained after fermentation for 18 h, and the tartaric and acetic acid contents were 4.819 and 2.218 times the contents obtained after fermentation for 18 h, respectively. The gamma-aminobutyric acid (GABA) content was about 2.156 times that obtained after fermentation for 18 h, and the total phenol content was about 1.717 times that of the unfermented rice. Compared with unfermented brown glutinous rice, the sourness and sweetness of sweet fermented brown glutinous rice were enhanced, and the main volatile components were increased significantly. Moreover, the DPPH free radical scavenging rate and Ferric reducing antioxidant power increased after fermentation, suggesting that fermentation improved the antioxidant capacity of brown glutinous rice. Compared with the traditional sweet fermented white glutinous rice, the sweet fermented brown glutinous rice has higher nutritional components, flavor and antioxidant activity.